Factors influence employee readiness to organizational changes among Institut Sukan Negara (ISN) Management Services Department / Muhamad Firdaus Abdul Rasak - Abdul Rasak, Muhamad Firdaus (Faculty of Business and Management, 2013)
The purpose of this study is to identify the factors influence readiness towards the organizational changes at Institut Sukan Negara (ISN) managing services departments. In addition, three factors are identified which is new technology, motivation to change and staff attributes. These three factors were examined whether having an impact towards a readiness to organization changes as well. This study has used a questionnaire to collect the data from Institut Sukan Negara (ISN) service department and lots of sources of articles to give asupport the variety of influence towards a readiness to organizational changes. The respondent which is involved in this study is four divisional departments which are Human Resources, Administration, Finance, and Property and Facilities. There are 60 respondents involved in this study. The researcher used Statical Package for Social Science (SPSS) version 21 to analyse the data. From the finding as well, analysis showed that there were positive impact for three variables which is new technology, motivation to change and staff attributes towards a readiness to organizational changes.